The Influence of Acetaminophen on Task Related Attention - Jaswal, Sumeet Mutti; Granados Samayoa, Javier A.; Kam, Julia W. Y.; Randles, Daniel; Heine, Steven J.; Handy, Todd C. (Frontiers in Neuroscience, 2019)
Our study was designed to examine whether the pain reliever acetaminophen impacts the normal ebb-and-flow of off-task attentional states, such as captured by the phenomenon of mind wandering. In a placebo-controlled between-groups design, participants performed a sustained attention to response task while event-related potentials (ERPs) to target events were recorded. Participants were queried at random intervals for their attentional reports – either “on-task” or “off-task”. The frequency of these reports and the ERPs generated by the preceding target events were assessed. Behaviourally, the frequency of off-task attentional reports was comparable between groups. Electrophysiologically, two findings emerged: first, the amplitude of the P300 ERP component elicited by target events was significantly attenuated during off-task vs. on-task attentional states in both the acetaminophen and placebo groups. Second, the amplitude of the LPP ERP component elicited by target events showed a significant decrease during off-task attentional states that was specific to the acetaminophen group. Taken together, our findings support the conclusion that acetaminophen doesn't impact our relative propensity to drift into off-task attentional states, but it does affect the depth of neurocognitive disengagement during off-task attentional states, and in particular, at the level of post-categorization stimulus evaluations indexed by the LPP.